Two new species of Eharius Tuttle & Muma (Acari: Phytoseiidae) from Turkey, with a key to world species - Döker İsmail (Zootaxa, 2018)
Two new species of the genus Eharius Tuttle & Muma (Acari: Phytoseiidae), Eharius karuti sp. nov. and Eharius stathakisi sp. nov. are described and illustrated, based on specimens collected from Phlomis sp. and Marrubium vulgare L. (Lamiaceae) from Turkey. A key to the known species of the genus is provided.